Branding local heritage and popularising a remote past: The example of Haugesund in Western Norway - Torgrim Sneve Guttormsen (AP, 2017)
Since the national romantic era, the Haugesund region of Norway has been associated with patriotism and heroism as it is believed to be the homeland of the Viking hero Harald Fairhair, the first king of Norway. In the arrival hall at the airport outside Haugesund the passengers are today faced with the following words: “Welcome to the Homeland of the Viking Kings”. The slogan refers to official regional attraction strategies based on a late modern Viking enthusiasm, used in efforts to increase local identity, to enchant a visitor market and to brand the region, in short, to create pride and glory. In this paper, dynamics of heritage production at Haugesund are examined by emphasising how a popular and commercial past (“the experience society”) mediates public debates and conflicts, thus questioning the function experts within the field of archaeology and the cultural heritage management have in local communities.